Opioid-Free Anesthesia in Ophthalmic Surgeries - Tantri, Aida Rosita; Angkasa, Hansen; Firdaus, Riyadh; Claudia, Tasya; Tantri, Ignatia Novianti (Indonesian Journal of Anesthesiology and Reanimation, 2023)
Introduction: Opioid-free anesthesia (OFA) is an alternative to Opioid based anesthesia (OBA) which uses multimodal analgesia to replace opioids. However, its feasibility, safety, and exact recommended combination remain debatable. Case Series: We administered OFA in 5 types of elective ophthalmic surgeries under general anesthesia in ASA 1-2 adult patients (evisceration, ocular exenteration, periosteal graft, scleral buckling, vitrectomy, and dacryocystorhinostomy) to assess the feasibility of OFA. We gave preoperative Paracetamol and Pregabalin with Dexmedetomidine as a loading dose (1 mcg/kg in 10 minutes) and maintenance at 0.7 mcg kg-1 per hour. Induction was performed using Propofol 1-2 mg kg-1, Lidocaine 1-1.5 mg kg-1 IV, and Rocuronium. Before the incision, Dexamethasone and Ranitidine were given. Maintenance was done using Dexmedetomidine and Sevoflurane. Fentanyl was used as rescue analgesia if required. Dexmedetomidine was stopped 15-30 minutes before the procedure ended. Metoclopramide and Ketorolac were given as postoperative management. Throughout the procedure, our patients had stable hemodynamics, did not experience life-threatening bradycardia, and did not require rescue analgesia. All patients regained full consciousness and did not experience postoperative nausea and vomiting, emergency delirium, or coughing. Conclusion: Multimodal analgesia was an excellent intraoperative OFA regimen as an alternative to OBA and provided controlled hypotension in ocular surgery. Safe OFA is possible with combined analgesia regimens, strict intraoperative monitoring, and adequate anesthesia depth.